CYBER SECURITY IN THE BALTIC SEA REGION: CYBER SECURITISATION IN FINLAND AND SWEDEN AFTER THE 2007 CYBER ATTACKS AGAINST ESTONIA - Rantanen, Teo (My University, 2019)
The topic of this thesis covers the cyber security development in the Baltic Sea Region, namely in Finland and Sweden. The aim of this thesis is to investigate the cyber securitisation processes of Finland and Sweden since the 2007 attacks against Estonia. The theoretical framework is derived from the Copenhagen School’s securitisation theory and it provides the foundation for the methods used in the analysis. The primary data is the speeches from high level Finnish and Swedish politicians, government programmes, and the cyber security strategies of both countries. The analysis is conducted by analysing the rhetoric and content of the selected material in the light of the securitisation criteria. The findings suggest that the cyber attacks against Estonia accelerated the cyber securitisation in Finland and only influenced the Swedish securitisation of cyber space which evolved slower than in Finland. Finland and Sweden should develop more proactive cyber security policies in order to follow the ever changing cyber landscape.
Keywords: cyber, security, securitisation, policy-making, Baltic Sea Region